Evaluation of Anticolitis and Antioxidant Properties of Bixa orellana (Bixaceae) Leaf Hydroethanolic Extract on Acetic Acid-Induced Ulcerative Colitis in Rats - Michel Archange Fokam Tagne, PhD; Blaise Kom, PhD; Angèle Foyet Fondjo, PhD; Paul Aimé Noubissi, PhD; Benjamin Talom Tangue, PhD; Estelle Flora Gaffo, MSc; Gaëtan Olivier Fankem, PhD; Henri Wambe, PhD; Joseph Ngakou Mukam, MSc; René Kamgang, HDR (Elsevier, 2022)
ABSTRACT: Background: Ulcerative colitis is an idiopathic inflammatory bowel disease characterized by tissue damage, diarrhea, anemia, and loss of body weight. Tissue damage occurs as a result of uncontrolled activation of the immune response and an increase in free radicals, which have a strong effect on the pathogenesis of inflammatory bowel disease. The incidence and prevalence of this inflammatory disease continue to increase worldwide. Maceration of Bixa orellana leaves in palm wine is used in traditional medicine to treat diarrhea, dysentery, and hemorrhoids in the Adamaoua region of Cameroon. Objective: The present work evaluated the preclinical effects (ie, antioxidant, hematological, and histological activities) of the hydroethanolic extract of Bixa orellana leaves in an in vivo, rat acetic acid-induced ulcerative colitis model. Methods: Thirty-six female rats weighing between 165 and 180 g were fasted for 18 hours and then anesthetized with ether. A dose of 1 mL acetic acid (5%) was administered rectally through a catheter in all rats except the normal control group, which received distilled water (1 mL) instead. Treatments began 48 hours after rectal administrations of acetic acid or water, and all animals were treated twice daily for 7 days. The normal control group and the colitis control group received PO distilled water (10 mL/kg), the positive control received orally loperamide (5 mg/kg, and the 3 test groups received orally the hydroethanolic extract of Bixa orellana at 100, 200, and 400 mg/kg, respectively. During treatment, the number of diarrheal stools and weight change were assessed. At the end of the treatment, the animals were put to death under ether anesthesia. Blood was collected postmortem for evaluation of hematological and antioxidant parameters. The abdomen was opened via a midline incision and the colon was removed and emptied of all contents to assess histological and antioxidant parameters. Results: During treatment, the number of diarrheal stools was significantly decreased from day 3 in animals treated with 100 (P < 0.05), 200 (P < 0.05), and 400 (P < 0.01) mg/kg extract compared with the colitis control group. The change in body weight of all extract-treated rats decreased significantly from day 3 (-5.55%; P < 0.05) to day 8 (-13.80%; P < 0.01) compared with the normal control. In the colitis control, this change ranges from -6.15% on day 2 to -15.13% on day 8. Extract treatment with 100, 200, and 400 mg/kg significantly reduced (P < 0.05) the number of lesions and the relative weight of the colon. The levels of red blood cells, neutrophils, and total white blood cells decreased in the colitis control group, whereas treatment with the extract at doses of 100, 200, and 400 mg/kg was associated with a significant increase in these hematological parameters. Catalase and superoxide dismutase activity and glutathione concentrations all increased significantly (P < 0.01) in blood and colon in all extract-treated animals, whereas levels of malondialdehyde and nitric oxide were significantly decreased (P < 0.01) compared with the colitis control animals. Conclusions: The hydroethanolic extract of Bixa orellana leaves had protective effects against acetic acid-induced ulcerative colitis in rats that was associated with inhibited production of free radicals believed to be responsible for oxidative stress, hematological disorders, and tissue damage in this animal model.